De quais jovens fala a literatura juvenil brasileira premiada pela FNLIJ de 2000 a 2017? - Oliveira-Iguma, Andreia Alencar (2019)
This study aims to analyze which young people speak the narratives awarded in the category “best for young”, from 2000 to 2017, by the National Children’s Book Foundation – FNLIJ. Research shows the incidence of three themes that permeate much of the selected corpus – the fracturing themes, the intertextualities and intermedialities, and the unusual – and of a central theme, which is thematic throughout the corpus – the self-discovery process of the character. Such themes were elected as guiding principles for the organization of the analysis in the thesis. To think about these themes, as a theoretical reference we will have the contributions made by Ramos; Navas (2016); Martha (2010; 2011); Hutcheon (1991); Gama-Khalil (2015; 2015); Michelli (2013). The justification regarding the fracturing themes comes from the recurrence of subjects that for a long time were considered taboos in the productions aimed at children and young audiences. Therefore, we believe it is important to highlight them in our analysis process; the intertextuality and the intermediality became recurrent in a significant part of the corpus. In this respect, we understand that the regularity of these resources within the system of youth literature needs to be analyzed; and, regarding the unusual, besides the recurrence of titles that bring the theme in its constructions, we also defend that the work with the fantastic is a significant possibility of reflection on social orders. This study also seeks from data systematized by researchers in the field, such as Alice Aurea Penteado Martha (2008, 2010), João Luís Ceccantini (2000, 2010), Malu Zoega Souza (2003), José Nicolau Gregorin Son (2016), Diana Navas (2016), to provide a brief historiography about the youth literature system, since its legitimacy is still recent, counting, therefore, with few studies. Moreover, in order to understand about youth, the social category for which our object of study is intended – the Brazilian youth literature –, it was essential to integrate readings capable of helping us in this process: for this, we chose the works developed as central in the field of sociology and psychoanalysis, among which we highlight Luís Groppo (2000), Contardo Calligaris (2000), Deleuze; Guattari (1995) and Zygmunt Bauman (2018). As will be evidenced throughout the thesis, we understand that youths are multiple and not limited to a delimited chronology, and for this reason, there are also many facets of the literature aimed at the youth audience.